Technology and urban form, Chicago 1830-1972 - Lindsay Falck (School of Architecture, Planning and Geomatics, 2024)
The purpose of this study is to trace the influences which are exerted on the urban environment by changing developments in technology, operating in combination with social, economic and political factors, and to study the results of these influences by observing the evolving forms and conditions of the city at particular points in time. The study also examines the converse situation where technology has in some cases been called on to provide new techniques, or systems of provision, to satisfy new demands caused by changing activity patterns in the city. In essence therefore, the study is concerned with the inter-relationships of "Opportunity and Response" and 'Need and Response", between urban factors and technological enterprise, and the resultant effects on the form and condition of the physical environment. It is axiomatic that the degree of influence of technology on the urban environment does vary over time. At some stages in general historical development, technological changes have been extremely slow, as for example in early Egypt, or in Western Europe between the fifth and ninth centuries, whereas at other points in time, technological development has occurred at a remarkable rate, as at the turn of this century in Europe and America, and currently in Africa, Asia and Latin America. It is also accepted that factors other than technology, such as war, economic depression, catastrophies, or human reactions to historical situations, have in some periods suppressed or drastically accelerated the effects of technological development. Such factors have been accounted for in the methods of study and presentation of the thesis, so that factors of change in technology and urban response are always seen in relation to other non-technical generative forces, in order to obtain a balanced view. Finally it must be clearly established from the outset that the term "technological development" does not automatically imply ''advancement", either in technical or in human value terms. The evident ills of some of man's inventions or innovations are constant reminders of his shortsightedness or incomprehension of the long term effects of his inventiveness.